Força e endurance muscular inspiratória em crianças e adolescentes com fibrose cística: comparação com indivíduos saudáveis - Vendrusculo, Fernanda Maria (Pontifícia Universidade Católica do Rio Grande do Sul, 2014)
Made available in DSpace on 2014-04-04T02:01:35Z (GMT). No. of bitstreams: 1 000456334-Texto+Completo-0.pdf: 876900 bytes, checksum: 9a3a16228d37d2decb9f9e991320abe6 (MD5) Previous issue date: 2014 === Objectives : To evaluate inspiratory muscle strength and endurance in children and adolescents with cystic fibrosis (CF) in comparison with healthy subjects. Methods : This cross-sectional observational study evaluated CF patients (6 to 18 years old) and healthy subjects paired in a 1:2 proportion, for sex, age, height and weight. Spirometry, impulse oscillometry, plethysmography, manovacuometry and a protocol of inspiratory muscle endurance were performed. Data were analyzed using Student’s t test and Pearson correlation coefficient. Results : Thirty four patients with CF were included in the study with a mean age of 12. 6±2. 9 years and twenty of them were boys (58. 8%). The mean percentage of maximal inspiratory pressure (MIP%) was 118. 5±25. 8 and the endurance (percentage of MIP) was 60. 9±13. 3. Sixty eight healthy subjects were included and they presented a mean MIP% of 105. 8±18. 0 and an endurance of 65. 3±12. 3 of. CF patients had higher MIP% than healthy subjects and no significant difference in the endurance was shown. When restricting the analysis to CF patients without colonization by Pseudomonas aeruginosa and with forced expiratory volume in one second (FEV1) greater than 80% of predicted values, MIP% values were significantly higher and inspiratory muscle endurance was lower, in comparison with the control group. MIP correlated more significantly with forced vital capacity (r=0. 44, p=0. 01) and FEV1 (r=0. 41, p=0. 01), while endurance correlated better with total airway resistance (r=0. 35, p=0. 04) and with central airway resistance (r=0. 48, p=0. 04).Conclusion : Children and adolescents with CF present changes in inspiratory muscle strength and endurance that are associated differently with levels of pulmonary impairment. Furthermore, the significant strength associations are better related to pulmonary function parameters, while endurance is to airway resistance. === Objetivos : Avaliar a força e a endurance muscular inspiratória em crianças e adolescentes com fibrose cística (FC) e comparar com indivíduos saudáveis.Métodos : Estudo observacional, transversal, em pacientes com FC (6 a 18 anos) e indivíduos saudáveis pareados na proporção de 1:2 por sexo, idade, altura e peso. Foram realizados espirometria, oscilometria de impulso, pletismografia, manovacuometria e protocolo de endurance muscular inspiratória. Para análise de dados utilizou-se os testes t de student e a correlação linear de Pearson. Resultados : Foram incluídos 34 pacientes com FC, média de idade de 14,0±2,7, sendo 20 pacientes (58,8%) do sexo masculino, com média de pressão inspiratória máxima percentual (PIMAX%) de 118,5±25,8 e de endurance (percentual da PIMAX) de 60,9±13,3. Também foram incluídos 68 indivíduos saudáveis com média de PIMAX% de 105,8±18,0 e de endurance de 65,3±12,3. Os pacientes com FC apresentaram maior PIMAX% do que os saudáveis e não apresentaram diferença significativa na endurance. Ao analisar separadamente os pacientes com FC sem colonização por Pseudomonas aeruginosa e com volume expiratório forçado no primeiro segundo (VEF1) maior do que 80% do previsto a PIMAX% foi significativamente maior nos pacientes com FC e a endurance muscular inspiratória foi menor em comparação com os saudáveis. A PIMAX se correlacionou com capacidade vital forçada (r=0,44; p=0,01) e com VEF1 (r=0,41; p=0,01) e a endurance se correlacionou com resistência total das vias aéreas (r=0,35; p=0,04) e com a resistência central das vias aéreas (r=0,48; p=0,04).Conclusão : Crianças e adolescentes com FC apresentam alterações da força e da endurance muscular inspiratória que são distintas em diferentes níveis de comprometimento pulmonar. Além disso, a força parece estar mais relacionada com parâmetros da função pulmonar e a endurance com a resistência das vias aéreas.